Pravin Gordhan : master juggler - Dorfling, Tamzyn; Beswick, Claire; Duffy, Neil ([London] : SAGE, 2016)
Pravin Gordhan, commissioner of the South African Revenue Services (SARS), had managed to improve tax collection substantially over his six years of office, whilst also managing to keep changing the institution internally. This book profiles the role of Gordhan's leadership in making such a complex public organisation operate efficiently.
Originally Published in: Dorfling, T., Beswick, C., & Duffy, N. (2007). Pravin Gordhan: Master Juggler (Abridged). WBS-2007-5. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; South African Revenue Service; Tax collection -- Management -- South Africa; Industrial management -- Case studies